2018
DOI: 10.4103/tcmj.tcmj_83_18
|View full text |Cite
|
Sign up to set email alerts
|

Individualizing medical treatment of overactive bladder

Abstract: Overactive bladder (OAB) syndrome is highly prevalent in both men and women and might have negative impact on quality of life. Clinical trials of OAB usually highly select participants that may not reflect the real-world practice of OAB patients. The spectrum of OAB includes patients with idiopathic, neuropathic, with bladder outlet obstruction, and patients in elderly and medical comorbidities. Patients might have poor response to OAB medication or have adverse events after treatment. Therefore, treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Further, these AEs lead to low adherence rates 18 . A new OAB drug is necessary so that physicians can adjust the dose and combine it with different medications to achieve the best efficacy and reduce AEs to the minimum possible 24 …”
Section: Discussionmentioning
confidence: 99%
“…Further, these AEs lead to low adherence rates 18 . A new OAB drug is necessary so that physicians can adjust the dose and combine it with different medications to achieve the best efficacy and reduce AEs to the minimum possible 24 …”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] Kuo et al recommend individualized treatment of overactive bladder syndrome patients. 29 In the famous SYMPHONY trial, Abrams et al observed that Mirabegron in combination with Solifenacin or Darifenacin gave better results in treatment of OAB than either drug alone. 30…”
Section: Discussionmentioning
confidence: 99%
“…OAB is highly prevalent and has an impact on patient quality of life. The current oral medications for OAB include antimuscarinics and beta-3 adrenoceptor agonists [6]. In patients refractory to these OAB medications, intravesical Botox injection has been documented to act as a third-line treatment according to the American Urological Association (AUA) and European Association of Urology guidelines [31,32].…”
Section: Botox Injection For Oabmentioning
confidence: 99%
“…OnabotulinumtoxinA (BOTOX ® ; Allergan, Irvine, CA, USA) was first used to treat patients with spinal cord injury having neurogenic detrusor overactivity (NDO) or detrusorsphincter dyssynergia [1][2][3][4]. Later, Botox was used for the treatment of idiopathic detrusor overactivity (IDO) and overactive bladder syndrome (OAB) refractory to conventional treatment [5][6][7]. Botox has been approved for these two clinical conditions, and it has been widely used to restore urinary continence and improve quality of life [8,9].…”
Section: Introductionmentioning
confidence: 99%